Dilated cardiomyopathy with Graves disease in a young child - Yu Jung Choi; Jun Ho Jang; So Hyun Park; Jin-Hee Oh; Dae Kyun Koh (Korean Society of Pediatric Endocrinology, 2016)
Graves disease (GD) can lead to complications such as cardiac arrhythmia and heart failure. Although dilated cardiomyopathy (DCMP) has been occasionally reported in adults with GD, it is rare in children. We present the case of a 32-month-old boy with DCMP due to GD. He presented with irritability, vomiting, and diarrhea. He also had a history of weight loss over the past few months. On physical examination, he had tachycardia without fever, a mild diffuse goiter, and hepatomegaly. The chest radiograph showed cardiomegaly with pulmonary edema, while the echocardiography revealed a dilated left ventricle with an ejection fraction (EF) of 28%. The thyroid function test (TFT) showed elevated serum T3 and decreased thyroid stimulating hormone (TSH) levels. The TSH receptor autoantibody titer was elevated. He was diagnosed with DCMP with GD; treatment with methylprednisolone, diuretics, inotropics, and methimazole was initiated. The EF improved after the TFT normalized. At follow-up several months later, although the TFT results again showed evidence of hyperthyroidism, his EF had not deteriorated. His cardiac function continues to remain normal 1.5 months after treatment was started, although he still has elevated T3 and high TSH receptor antibody titer levels due to poor compliance with drug therapy. To summarize, we report a young child with GD-induced DCMP who recovered completely with medical therapy and, even though the hyperthyroidism recurred several months later, there was no relapse of the DCMP.